Enhancing listeners’ social well-being through radio listening: a qualitative study among Klang Valley radio listeners - Farah Fazlinda Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2023)
Radio has been known as one of the oldest forms of mass communication. It has served its purpose of entertaining and informing people for decades. With the advancement of technology, audiences now have more ways to access an increasing amount of information. However, radio continues to play an important role in today's world. Radio is about more than just announcers, news, and music. Radio is about companionship and connecting emotionally with the listener. Previous research discovered that radio has a significant impact on people's lives. Thus, this research aims to comprehend people's preferences for listening to Astro radio stations in the current environment. Besides, it aims to explore the impact of streaming on listeners’ listening experiences. This research employed a qualitative research method using focus group discussion. Thirty ASTRO radio listeners were recruited based on criteria including age, radio channel preference, and SYOK app usage. This research is expected to discover the radio listeners’ motivations for listening to ASTRO Radio channels, understand the impact of the SYOK app in influencing their preference towards radio listening, and discover the role of radio content in enhancing the listeners’ well-being. It is expected that the research findings obtained from the focus group discussion can provide some recommendations to improve the radio content and the SYOK app content.